Metabolomic analysis of Streptococcus pneumoniae: uncovering key metabolic pathways - Jiang, Haiyan; Zhao, Changliang; Feng, Lu; Gao, YuJun; Mi, Zhihui; He, Haiying (Frontiers in Microbiology, 2025)
BackgroundPneumococcal infection, caused by Streptococcus pneumoniae, is a prevalent cause of community-acquired pneumonia and a major pathogen responsible for illnesses such as meningitis, sepsis, and pharyngitis. The complex etiology of S. pneumoniae infection poses significant challenges in elucidating the molecular mechanisms underlying its pathogenesis.MethodsIn this study, twenty serum samples from individuals infected with S. pneumoniae and fifteen serum samples from normal controls were analyzed using liquid chromatography/mass spectrometry (LC–MS) to identify metabolites. Multivariate statistical analyses, including principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA), were used to identify potential metabolites. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis was employed to map the metabolic pathways associated with these metabolites.ResultsThrough comparative analysis of the metabolic profiles of infected individuals and normal controls, we identified 418 metabolites that significantly contributed to the differentiation of group samples. The identified metabolites were categorized into various groups, such as amino acids, fatty acids, and phosphatidylcholine, and were enriched in pathways including galactose metabolism, the hypoxia-inducible factor-1 (HIF-1) signaling pathway, the citrate cycle, the pentose phosphate pathway, and glycolysis/gluconeogenesis. S. pneumoniae infection induced significant variations in the serum metabolome, with activation of metabolic pathways implicated in the immune response.ConclusionOur study provides a comprehensive and real-time analysis of the metabolic network, elucidating the complex processes that occur following pathogen invasion in the human body. The identification of metabolic biomarkers and enriched pathways lays a foundational framework for research and offers visualizable targets for the diagnosis and treatment of pneumococcal infections.